Computation of Greeks in LIBOR models driven by time–inhomogeneous Lévy processes. Issue 3 (3rd May 2016) - Eberlein, Ernst; Eddahbi, M'hamed; Lalaoui Ben Cherif, S. M.
ABSTRACT: The aim of this article is to compute Greeks, i.e. price sensitivities in the framework of the Lévy LIBOR model. Two approaches are discussed. The first approach is based on the integration-by-parts formula, which lies at the core of the application of the Malliavin calculus to finance. The second approach consists of using Fourier-based methods for pricing derivatives. We illustrate the result by applying the formula to a caplet price where the jump part of the driving process of the underlying model is given by a time–inhomogeneous Gamma process and alternatively by a Variance Gamma process.